2021
DOI: 10.1177/01945998211032897
|View full text |Cite
|
Sign up to set email alerts
|

Face, Content, and Construct Validity of a Virtual Reality Otoscopy Simulator and Applicability to Medical Training

Abstract: Objective Otologic diseases are common in all age groups and can significantly impair the function of this important sensory organ. To make a correct diagnosis, the correct handling of the otoscope and a correctly performed examination are essential. A virtual reality simulator could make it easier to teach this difficult-to-teach skill. The aim of this study was to assess the face, content, and construct validity of the novel virtual reality otoscopy simulator and the applicability to otologic training. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…In addition, Fukuta et al ( 46 ) generated a virtual operating theater orientation to improve knowledge and confidence of medical undergraduates. Except five validation studies of virtual simulators ( 26 , 47 , 53 , 65 , 81 ) in which the undergraduates acted as the novice group for comparison with the skilled group, the findings of all the other included studies positively supported the usability and its feasibility of integrating VS in surgical training.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, Fukuta et al ( 46 ) generated a virtual operating theater orientation to improve knowledge and confidence of medical undergraduates. Except five validation studies of virtual simulators ( 26 , 47 , 53 , 65 , 81 ) in which the undergraduates acted as the novice group for comparison with the skilled group, the findings of all the other included studies positively supported the usability and its feasibility of integrating VS in surgical training.…”
Section: Resultsmentioning
confidence: 90%
“…This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education. Moreover, only one third of (31) articles ( 15 , 16 , 22 , 26 , 31 33 , 38 , 47 , 48 , 52 , 53 , 56 , 58 , 60 – 62 , 64 , 65 , 67 , 71 , 73 , 75 , 76 , 78 80 , 95 , 96 , 101 , 105 ) included in this review were based on the commercially available or free VS softwares/platforms, the rest used the self-developed ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used in this study is the Research and Development (R&D) method which can be referred to as research and development through a literature review approach with measurement data and Confirmatory Factor Analysis (CFA) data analysis techniques and intends to test the validity of construct measurements on engineering mechanics [17,[25][26]. Construct validity proves that these measurements can confirm the indicators in the instrument items in measuring engineering mechanics learning competencies [27].…”
Section: Methodsmentioning
confidence: 99%
“…Es handelt sich hierbei um Präsentationsformen, die dazu geeignet sind, abstrakte räumliche Informationen, die den Augen des Betrachters unter normalen Umständen nicht unmittelbar zugänglich sind, erfahrbar zu machen [ 24 ]. Es können aber auch weniger spektakuläre, klinische Routineuntersuchungen mithilfe der VR patientenunabhängig zu Ausbildungszwecken eingesetzt werden [ 1 ], was in Zeiten der Corona-Pandemie eine enorme Hilfe bei der Aufrechterhaltung von Präsenzunterricht war und ist [ 17 ]. Die Maximalvariante einer solchen realitätsnahen Simulation wird als „immersive patient simulator“ (IPS) bezeichnet [ 8 ].…”
Section: Diskussionunclassified